Two nematode species of the family Tobrilidae (Enoplida) De Coninck, 1965 from Lake Baikal, Russia - Gagarin, Vladimir G.; Naumova, Tatyana V. (Zootaxa, 2011)
Two nematode species found in Lake Baikal, Gorevoi Utes (Russia) are presented. Eutobrilus mirandus sp. n. differs from all other species of the genus Eutobrilus by the markedly anterior position of the vulva (V=26–31%). The new species is similar to E. andrassyi Altherr, 1963 in body size and stoma structure but differs in the comparatively thicker body (males, a = 32–45 versus a = 60–75), shorter stoma (males, 26–27 µm long versus 35–40 µm long), longer spicules (48–53 µm versus 40 µm), and absence of crystalloids. A redescription and new illustrations of Paratrilobus delicatus (Shoshin, 1988) Andrássy, 2007, including a description of the previously unknown females, are also given.